Register as a tool to revolutionize language teaching and learning - Yeob, Shamsul Jamili; Khaza’ai, Nuwairi (Common Ground Publisher, 2008)
Language teaching and learning has undergone great changes over time. Learners are functional in their actions when learning languages. Learners have their aims and goals when learning a language. At the same time, learners want to spend less time to master a language effectively. This paper shares the Malaysian experience in establishing strong academic foundation among students in primary, secondary and even tertiary education. The sociolinguistics experience in Malaysia sees tremendous success in using Malay language as the medium of communication in schools at all level. Mastering the variety of language used in the specific area will be useful for the students in their practice later. The variety of language referred is Register. Over two decades Bahasa Melayu proved to be able to perform well in its functions locally and internationally in various fields at all levels. Unfortunately, Arabic has no similar experience as Malay Language in promoting register as a tool in teaching and learning language, yet, due to its capability as the language of Quran it manages to accommodate with the language developments. Thus, this paper attempts to reveal Malay language capability in adopting the concept of register as an effective tool in teaching language and learning. Research sees the same effect in registers of Arabic too.